Lunturnya Rasa Cinta Tanah Air Orang Aboru di Negeri Aboru - Johan Tanamal; Matheus Rumaratu; Amir Tuakia (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2021)
The purpose of this study was to determine the extent of the The objective of this essay is to examine the aboru people'sattitudes about the unitary state of the Republic of Indonesia (NKRI), as well as the internal and external reasons that contributeto their loss of love for their motherland. The focus of this study is on the Aboru people's perceptions of the Republic of Indonesia as a unitary state, as well as the internal and external variables that influence it. The study's findings reveal that there are differing perspectives on the Republic of Indonesia's unitary state, with those in favor of the unitary state outnumbering those in favor of the Maluku liberation movement, which the Aboru people appear to be quite enthusiastic about in marking the Republic of South Maluku's (RMS) Independence Day, which falls on April 25 every year. Meanwhile, the perceived injustice, both in the handling of nature and at the level of the Indonesian bureaucracy, is the internal influence behind the collapse of Aboru Nationalism. External elements that influence them include the media's influence and liberalism's worldview, which drives them to be unconcerned about the government.